2008
DOI: 10.2478/s11686-008-0036-5
|View full text |Cite
|
Sign up to set email alerts
|

Helminth parasites in native and invasive mammal populations: comparative study on the Barbary ground squirrel Atlantoxerus getulus L. (Rodentia, Sciuridae) in Morocco and the Canary Islands

Abstract: A total of 51 and 21 adults of Barbary ground squirrels (Atlantoxerus getulus) were trapped during May-July 2006 from the introduced populations on Fuerteventura Island (Canary Islands) and the native populations in Morocco, respectively. One trematode, 1 cestode and 4 nematode species were recovered belonging to five families: Brachylaima sp. (Brachylaimidae), Catenotaenia chabaudi (Catenotaeniidae), Protospirura muricola (Spiruridae), Dermatoxys getula and Syphacia pallaryi (Oxyuuridae), and Trichostrongylus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 29 publications
(31 reference statements)
0
9
0
Order By: Relevance
“…Our study suggests that the low parasite species richness in the wood mouse at the study site in Algeria could be the consequence of the human introduction of this host. The loss of parasites in the event of a host introduction has been reported in introduced populations of A. sylvaticus on islands (Goüy de Bellocq et al, 2003), and in other rodents such as the squirrel Atlantoxerus getulus, introduced into the Canary Islands from Morocco (López-Darias et al, 2008). However, it is important to note that the small sample size in our study probably underestimates the full parasite specific richness, as indicated by Feliu et al (1997).…”
Section: Discussionmentioning
confidence: 56%
“…Our study suggests that the low parasite species richness in the wood mouse at the study site in Algeria could be the consequence of the human introduction of this host. The loss of parasites in the event of a host introduction has been reported in introduced populations of A. sylvaticus on islands (Goüy de Bellocq et al, 2003), and in other rodents such as the squirrel Atlantoxerus getulus, introduced into the Canary Islands from Morocco (López-Darias et al, 2008). However, it is important to note that the small sample size in our study probably underestimates the full parasite specific richness, as indicated by Feliu et al (1997).…”
Section: Discussionmentioning
confidence: 56%
“…These hypotheses have been considered to explain the lack of helminth richness in two other introduced mammal species on the Canary Islands, i.e. the rabbit Oryctolagus cuniculus (L., 1758) [ 18 ] and the Barbary ground squirrel Atlantoxerus getulus (L., 1758) [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The species has negative ecological, economical, and public health impacts. They consume native and endemic snails (Machado and Domínguez 1982;Groh and García 2004;López-Darias 2007), prey upon some critically endangered species (Bañares et al 2003), and feed upon the eggs of small native and endemic passerine birds (López-Darias 2007). Their ecological impacts go beyond direct predation upon species, as they alter plant-animal interactions of fleshy-fruited plant species and ruderal weeds, including herbaceous plants of native or introduced origin (López- Darias andNogales 2008, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…They consume native and endemic snails (Machado and Domínguez 1982;Groh and García 2004;López-Darias 2007), prey upon some critically endangered species (Bañares et al 2003), and feed upon the eggs of small native and endemic passerine birds (López-Darias 2007). Their ecological impacts go beyond direct predation upon species, as they alter plant-animal interactions of fleshy-fruited plant species and ruderal weeds, including herbaceous plants of native or introduced origin (López- Darias andNogales 2008, 2016). Competition with the endemic shrew, Crocidura canariensis, listed as vulnerable by the IUCN (Hutterer 2008), is suggested Traveset et al 2009), but no quantitative and conclusive data are available.…”
Section: Introductionmentioning
confidence: 99%